Dampak Implementasi Perdagangan Bebas pada Sektor Ekonomi di Indonesia - Yerlen Sri Mentari Pombu; Hari Yeni (Syntax Idea)
This research aims to conduct an analysis of the impact of the implementation of free trade on the economic sector in Indonesia. In the context of international trade which is increasingly important for the world economy, the implementation of free trade has become a hotly debated topic because the positive side in terms of economic improvement is also balanced by the negative side in terms of trade imbalances and its influence on national policy. This research was carried out by conducting a literature study that collected various previous studies regarding the advantages and disadvantages of free trade. The results of the discussion show that the implementation of free trade can provide benefits for the country, such as increasing exports and imports, foreign direct investment, and increasing economic growth. However, on the other hand, the implementation of free trade can also result in losses, such as loss of jobs and negative environmental impacts. This research emphasizes the importance of managing free trade to ensure that trade profits and losses are distributed fairly and avoid the possibility of being exploited by stronger parties.